Investigation of heated fins geometries on the heat transfer of a channel filled by hybrid nanofluids under the electric field. (December 2021) - Ben Hamida, Mohamed Bechir; Hatami, Mohammad
Abstract: In this study, Galerkin Finite Element Method or GFEM is used for modeling the heat transfer in a channel filled by hybrid nanofluids under the electric field. Three voltages of 1, 3 and 5V are supplied to the inlet boundary condition and four types of hybrid nanofluid were used (TiO2 –CuO, TiO2 –Al2 O3, Al2 O3 –CuO and Al2 O3 –Cu) to improve the average Nusselt number. 11 different cases also were proposed to examine the effect of fins geometries on the heat transfer by Central composite design (CCD). Number of fins (4–8), length of fins (10–20 cm) and thickness of fins (2–4 cm) are the considered variables and levels. Results indicated that TiO2 –Al2 O3 with ϕ=0.05 had the greatest Nusselt number among the other experienced cases. Also, increasing the nanoparticles concentrations by 0.01 could improve the Nusselt number up to 5.19%. Furthermore, Results showed that increasing the supplied voltage for electric field from 1V to 5V can improve the heat transfer process in the channel.